A Single Nucleotide Polymorphism Translates into a Radical Amino Acid Substitution at the Ligand-Binding Site in Fasciola hepatica Carboxylesterase B - Miranda-Miranda, Estefan (2022)
Fil: Miranda-Miranda, Estefan. Instituto Nacional de Investigaciones Forestales Agrícolas y Pecuarias. Centro Nacional de Investigaciones Disciplinarias en Salud Animal e Inocuidad. Departamento de Artropodología; México.